The Better angels of our nature : why violence has declined - Pinker, Steven, 1954- (New York : Penguin Books, 2011)
We've all asked, "What is the world coming to?" But we seldom ask, "How bad was the world in the past?" Cognitive scientist Steven Pinker shows that the past was much worse. Evidence of a bloody history has always been around us: genocides in the Old Testament, gory mutilations in Shakespeare and Grimm, monarchs who beheaded their relatives, and American founders who dueled with their rivals. The murder rate in medieval Europe was more than thirty times what it is today. Slavery, sadistic punishments, and frivolous executions were common features of life for millennia, then were suddenly abolished. How could this have happened, if human nature has not changed? Pinker argues that thanks to the spread of government, literacy, trade, and cosmopolitanism, we increasingly control our impulses, empathize with others, debunk toxic ideologies, and deploy our powers of reason to reduce the temptations of violence.
A foreign country. Human prehistory ; Homeric Greece ; The Hebrew bible ; The Roman Empire and early Christendom ; Medieval knights ; Early modern Europe ; Honor in Europe and the early United States ; The 20th century -- The pacification process. The logic of violence ; Violence in human ancestors ; Kinds of human societies ; Rates of violence in state and nonstate societies ; Civilization and its discontents -- The civilizing process. The European homicide decline ; Explaining the European homicide decline ; Violence and class ; Violence around the world ; Violence in these United States ; Decivilization in the 1960s ; Recivilization in the 1990s -- The humanitarian revolution. Superstitious killing : human sacrifice, witchcraft, and blood libel ; Superstitious killing : violence against blasphemers, heretics, and apostates ; Cruel and unusual punishments ; Capital punishment ; Slavery ; Despotism and political violence ; Major war ; Whence the humanitarian revolution? ; The rise of empathy and the regard for human life ; The republic of letters and enlightenment humanism ; Civilization and enlightenment ; Blood and soil -- The long peace. Statistics and narratives ; Was the 20th century really the worst? ; The statistics of deadly quarrels, Part 1 : the timing of wars ; The statistics of deadly quarrels, Part 2 : the magnitude of wars ; The trajectory of great power war ; The trajectory of European war ; The Hobbesian background and the ages of dynasties and religions ; Three currents in the age of sovereignty ; Counter-enlightenment ideologies and the age of nationalism ; Humanism and totalitarianism in the age of ideology ; The Long Peace : some numbers ; The Long Peace : attitudes and events ; Is the Long Peace a nuclear peace? ; Is the Long Peace a democratic peace? ; Is the Long Peace a liberal peace? ; Is the Long Peace a Kantian peace? -- The new peace. The trajectory of war in the rest of the world ; The trajectory of genocide ; The trajectory of terrorism ; Where angels fear to tread -- The rights revolutions. Civil rights and the decline of lynching and racial pogroms ; Women's rights and the decline of rape and battering ; Children's rights and the decline of infanticide, spanking, child abuse, and bullying ; Gay rights, the decline of gay-bashing, and the decriminalization of homosexuality ; Animal rights and the decline of cruelty to animals ; Whence the rights revolutions? ; From history to psychology -- Inner demons. The dark side ; The moralization gap and the myth of pure evil ; Organs of violence ; Predation ; Dominance ; Revenge ; Sadism ; Ideology ; Pure evil, inner demons, and the decline of violence -- Better angels. Empathy ; Self-control ; Recent biological evolution? ; Morality and taboo ; Reason -- On angels' wings. Important but inconsistent ; The pacifist's dilemma ; The Leviathan ; Gentle commerce ; Feminization ; The expanding circle ; The escalator of reason ; Reflections.
Includes bibliographical references (p. 697-737, 739-771) and index.
Keywords: Violence -- Psychological aspects; Violence -- Social aspects; Nonviolence -- Psychological aspects